2021
DOI: 10.1016/j.celrep.2021.109422
|View full text |Cite
|
Sign up to set email alerts
|

Immune mechanisms orchestrate tertiary lymphoid structures in tumors via cancer-associated fibroblasts

Abstract: Tumor-associated tertiary lymphoid structures (TA-TLS) are associated with enhanced patient survival and responsiveness to cancer therapies, but the mechanisms underlying their development are unknown. We show here that TA-TLS development in murine melanoma is orchestrated by cancer-associated fibroblasts (CAF) with characteristics of lymphoid tissue organizer cells that are induced by tumor necrosis factor receptor signaling. CAF organization into reticular networks is mediated by CD8 T cells, while CAF accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
91
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 131 publications
(95 citation statements)
references
References 96 publications
(111 reference statements)
3
91
1
Order By: Relevance
“…However, the mechanisms underlying TLS development remain unclear. Rodriguez et al found that the organization of cancer-associated fibroblasts into reticular networks depends on tumor necrosis factor receptor signaling, which acts as a lymphoid tissue organizer [ 83 ]. Cancer-associated fibroblasts secrete CXCL13 to recruit CXCR5 + B cells expressing lymphotoxin-α1β2, which expands TLSs in the tumor microenvironment.…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanisms underlying TLS development remain unclear. Rodriguez et al found that the organization of cancer-associated fibroblasts into reticular networks depends on tumor necrosis factor receptor signaling, which acts as a lymphoid tissue organizer [ 83 ]. Cancer-associated fibroblasts secrete CXCL13 to recruit CXCR5 + B cells expressing lymphotoxin-α1β2, which expands TLSs in the tumor microenvironment.…”
Section: The Expression and Implications Of Cxcl13/cxcr5mentioning
confidence: 99%
“…Rodriguez et al studied cancer-associated fibroblasts to determine the effects of TLSs in a melanoma and colon adenocarcinoma mouse model [ 83 ]. Anti-PD-L1 and a combination of anti-PD-1 and anti-CTLA4 both increase the formation of TLSs in the tumor microenvironment, resulting in reduced tumor growth, and increased T cell recruitment to the tumor, as indicated by the formation of discrete T cell and B cell zones.…”
Section: The Cxcl13/cxcr5 Signaling Axis In the Ici Response Of Preclinical Modelsmentioning
confidence: 99%
“…In autoimmune disorders, TLSs are associated with production of the autoantibodies that drive disease progression; conversely, TLS formation correlates with good patient outcomes for many cancer types, suggesting that TLSs potentially promote anti-tumour immune responses ( Pipi et al, 2018 ). Similarly to lymph nodes, TLSs can exhibit segregated B- and T-cell zones ( Da Graça et al, 2021 ; Rodriguez et al, 2021 ), and are supported by stromal cells including FDCs, endothelial cells and fibroblasts ( Da Graça et al, 2021 ; Mitsdoerffer and Peters, 2016 ). The mechanisms of TLS initiation are not fully understood, but are likely to be driven by infiltrating cells and context-dependent inflammatory cues ( Mitsdoerffer and Peters, 2016 ; Rodriguez et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to lymph nodes, TLSs can exhibit segregated B- and T-cell zones ( Da Graça et al, 2021 ; Rodriguez et al, 2021 ), and are supported by stromal cells including FDCs, endothelial cells and fibroblasts ( Da Graça et al, 2021 ; Mitsdoerffer and Peters, 2016 ). The mechanisms of TLS initiation are not fully understood, but are likely to be driven by infiltrating cells and context-dependent inflammatory cues ( Mitsdoerffer and Peters, 2016 ; Rodriguez et al, 2021 ). Similarly to lymph node development, FAP + stromal cells can initiate lymphatic aggregates in response to inflammation ( Denton et al, 2019 ), requiring the presence of lymphotoxin for TLS formation and maintenance ( Mitsdoerffer and Peters, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation